Administrative control in eco-efficient management of water and energy: study an institution of higher education (REICE: Revista Electrónica de Investigación en Ciencias Económicas, 2020)
The objective of the research was to determine the relationship between administrative control and the eco-efficiency of water and electricity in the Faculty of Business Sciences of the National University of Education Enrique Guzmán y Valle, Peru in 2018. The methodology used was quantitative approach, non-experimental design, cross-sectional, descriptive and correlational. The sample was 274 people chosen at random from among teachers, administration staff and students. A structured questionnaire was applied for each study variable, with assessment scales to measure their relationships. The data were processed with the SPSS 24 program, which showed that the data did not have a normal distribution and were analyzed by Spearman's nonparametric R test. A very strong correlation between the study variables (r > 0.5) and the significant variables (Sig. < 0.05) was obtained.  Likewise, a very strong and significant correlation was observed between the variables water eco-efficiency and electrical energy, which demonstrated co-linearity. It is recommended to promote activities in favor of the eco-efficiency of the use of water and electricity resources so that the community itself contributes to the adequate use of resources with the least environmental impact.
Keywords: Eco-efficiency, water management, electricity, administrative control.